2019
DOI: 10.1111/mice.12487
|View full text |Cite
|
Sign up to set email alerts
|

A spatially explicit model of postdisaster housing recovery

Abstract: Although post-disaster housing recovery is an important player in community recovery, its modeling is still in its infancy. This research aims to provide a spatial regression model for predicting households' recovery decisions based on publicly available data. For this purpose, a hierarchical Bayesian geostatistical model with random spatial effects was developed. To calibrate the model, households' data that were collected from Staten Island, New York in the aftermath of Hurricane Sandy were used. The model r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Risk analysis simulations to advance the execution and efficiency decision making before and after disastrous events (Salgado et al, 2016), fragility curves in quantifying structural damage after a natural disaster (Kammouh et al, 2018a), and the implementation of performance-based earthquake engineering frameworks to model the post-earthquake recovery of a community of residential houses (Burton et al, 2015) have all contributed into finding a solution for bettering our communities' resilience. Nejat et al (2019) used a spatial regression model to predict households' recovery decisions from data available of the aftermath of Hurricane Sandy.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…Risk analysis simulations to advance the execution and efficiency decision making before and after disastrous events (Salgado et al, 2016), fragility curves in quantifying structural damage after a natural disaster (Kammouh et al, 2018a), and the implementation of performance-based earthquake engineering frameworks to model the post-earthquake recovery of a community of residential houses (Burton et al, 2015) have all contributed into finding a solution for bettering our communities' resilience. Nejat et al (2019) used a spatial regression model to predict households' recovery decisions from data available of the aftermath of Hurricane Sandy.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…Housing recovery is affected by many drivers and requires a collective effort to be understood [36]. These drivers can be broadly categorized into three groups: internal, interactive, and external drivers [37]. Internal drivers are individual and household-level factors that influence recovery, such as demographic and socioeconomic attributes, experience of past disasters, and level of damage.…”
Section: Drivers Of Recoverymentioning
confidence: 99%
“…The study also suggested that resource scarcity should be accounted in simulations to reflect the real situations during housing recovery. Nejat et al (2020) developed a regression model focusing on the factors affecting household' recovery decisions. Authors divided drivers of housing recovery into three categories of internal (i.e.…”
Section: Introductionmentioning
confidence: 99%